PENGATURAN KOMISI YUDISIAL DALAM KONSTITUSI: SUATU PERBANDINGAN ANTARA INDONESIA DAN THAILAND - Netty SR Naiborhu (Lembaga Kajian Hukum, Fakultas Hukum, Universitas Singaperbangsa Karawang, 2018)
In this paper, the author wants to compare the existence of KY in Indonesia with Thailand both in terms of its position in the constitution. Given the existence of the constitution can be said to be the rule of the game where its position as the highest source of law in a country. The reasons for the author: first, that speaking of KY there is a common thread with one of the principles, namely the judicial authority that is free. So speaking of the world of justice has become a fact in any country; secondly, the authors argue that the legal traditions carried out in Thailand at least have in common; third, the authors assume that someday Indonesia and Thailand as ASEAN member countries and have entered the era of the ASEAN Community (ASEAN Community) one day each institution will coordinate in the field of law, especially in the judiciary. The research method used in this study is a qualitative method through the approach of normative juridical methods which is also called library law research. The results showed the existence of KY as an institution in the field of judicial power both in Indonesia and Thailand is regulated in each constitution, which distinguishes between Indonesia and Thailand in terms of constitutional formulation, while the difference between KY in Indonesia and Thailand namely KY in Indonesia does not differentiate its existence in any judicial body. So that in carrying out its duties and authority can be done in collaboration with the existence of the Supreme Court. In contrast to Thailand, where the existence of KY is divided into two namely, the Judicial Commission of The Court and the Judicial Commission of Administrative Court. So that each KY only carries out his duties and authority within the judicial environment which is regulated in each judicial environment.